Personal scope of the obligation to maintaining cleanliness and order on the property - Szalewska, Małgorzata (Polish Yearbook of Environmental Law, 2020)
Pursuant to the Act on Maintaining Cleanliness and Order on Real Estate, the statutory obligations related to maintaining cleanliness and order on real estate – including the payment obligations resulting from the legal model of municipal waste management – have been assigned to the real estate owner. At the same time, for the purposes of this particular legal regulation, the legislator has introduced a separate definition of the real estate owner, thus including not only the owner from the civil perspective, but also other entities managing the real estate, including co-owners, perpetual usufructuaries and organizational units and persons managing or using real estate. The adoption in the Act on Maintaining Cleanliness of a broad, scope definition of the owner of real estate causes, in specific factual situations, serious doubts as to the actual scope of personal obligations under the Act on Maintaining Cleanliness. The subject of this article is to present the definition of the property owner adopted in the Act on Maintaining Cleanliness as a determinant of the scope of obligations arising from this Act.